EFFECTIVENESS OF STRYCHNOS LIGUSTRINA BL. EXTRACT AS FEED SUPPLEMENTATION TO INCREASE IMMUNE SYSTEM OF NILE TILAPIA (OREOCHROMIS NILOTICUS) WICH AGAINTS STREPTOCOCCUS AGALACTIAE - Zubaidah, Anis; Faidah, Kuny Riski; Samsundari, Sri (University of Muhammadiyah Malang)
One of the problems of intensive cultivation of tilapia is the attack of Streptococcosis disease caused by Streptococcus agalactiae bacteria. To prevent it is necessary to prevent the use of natural antibiotics that is Strychnine bush extract. The method used in this research is the experimental method using Completely Randomized Design (RAL), then the data is analyzed by using ANAVA. In this research, there were five treatments with various dosages, namely treatment (K: 0%), (A: 5%), (B: 10%), (C: 15%) and (D: 20%), each treatment was repeated four times. The main parameters used are hematocrit level, leukocrit level, leukocyte count and phagocytosis activity. As a supporting parameter is water quality and MIC (Minimum Inhibitation Concentration) test. The results showed that dosage of Strychnine bush extract did not affect the level of hematocrit and leukocrit level, but significant effect on leukocyte count with the highest value at treatment B with 10% dose is 11,9 × 105 cell / mm3. Giving extract also significant effect on phagocytosis activity with the highest phagocytosis value at treatment B with dose of 10% that is 32%.Keywords: Imune system, Streptococcosis, antibiotics, Minimum Inhibitation Concentration